Nutritional analysis of formulated infant food using sweet potatoes, soybeans, and shrimp - Dumagu, Melody (University of Cape Coast, 2025)
This study explores the utilisation of soybean flour, orange-fleshed sweet potatoes, and shrimp in infant food, as well as a small addition of tomatoes and onions. Soybean seeds, orange-fleshed sweet potatoes, shrimp, tomatoes, and onions were processed into powder. To achieve the various formulations, Minitab software was used: 80%:10%, 78%:12%, 75%:15%, 72%:18%, and 70%:20% of soybean and orange-fleshed sweet potato composite flour. Also, 10% shrimp, 5% tomatoes, and onion powder were added, and 100% OFSP was used as a control sample. Quality indicators like functional properties, nutritional composition, mineral content, and consumer acceptability of the infant food developed thereof were determined. Finally, the bulk density decreases from (0.69g/cm3 to 0.63g/cm3, while swelling capacity, water absorption capacity, oil absorption capacity, and solubility index increase from (16.83 to 17.89), (214.85% to 244.07%), (217.33% to 255.49%), and (16.31 to 18.15). Increasing the soybean flour fortification from 70% to 80% in infant food significantly increases the moisture content (8.78% to 10.39%), protein (25.25% to 33.11%), and fibre (7.56% to 8.87%) while decreasing the carbohydrate content from (43.19% to 27.65%) respectively. There was an improvement in the mineral content (phosphorus, iron, potassium, and zinc) of the orange-fleshed sweet potato soybean flour-fortified infant food. Furthermore, vitamin C significantly increased, and beta-carotene decreased with an increase in the inclusion of soybean flour in the infant food. Moreover, consumer acceptability of the infant food was enhanced after the soybean flour was added. These results may be relevant for improving the utility of soybean flour and orange-fleshed sweet potato, shrimp, and onion in the food industry.
xii, 117p:, ill
Keywords: Consumer acceptability; Infant Food; Nutritional composition; Orange-fleshed sweet potato; Soybean flour